The Sintesis Dan Karakterisasi Karbon Aktif Dari Limbah Biomassa Reject Pulp Sebagai Adsorben Zat Warna: Reject pulp - Sri Hilma Siregar; Hasmalina Nasution; Wirdati Irma; Dedi Suwito; Aulia Rizki Rahmadani; Sha-Ling Han (Acta Chimica Asiana, 2023)
This study examines the design of a heat exchanger (HE) in the production process of nickel ferrite (NiFe2O4) nanoparticles using the coprecipitation method by determining the shell and tube heat exchanger. The Microsoft Excel application is used as a manual calculating machine to facilitate the analysis of heat exchanger (HE) data calculations. The research flowchart starts with a literature study, preparation of tools and materials for design, calculation of the main shell and tube components, and then fabrication. Based on the calculation results, the design specification data for a shell and tube heat exchanger has a shell diameter of 0.032 m, a shell length of 4.267 mm, a thickness of 0.002 m with an initial heat transfer rate (Q) of 460130 W resulting in a heat transfer efficiency of 95.706% and an NTU of 6.165. The high effectiveness value makes the design of the one shell and tube type turbulent flow heat exchanger (HE) considered to have met the standards of high effectiveness and good performance. The design and design process is complete if the device functions properly. This study can be used as a reference for researchers in designing heat exchangers during production to make them more effective, reliable, and economical.